Semi classical quantum dots in their own micro cavity - Sánchez Pérez, Karla J.; García-Melgarejo, J. C.; Sánchez-Mondragón, J. J. (Acta Universitaria, 2013)
Among quantum dots there is an interaction called Foerster interaction, it consists on the transfer of one exciton from a quantum dot to another in a non-radiative energy transfer mechanism. In this work, we develop a model of the interaction of a pair of coupled Quantum Dots (QDs), each one in its own micro cavity, interacting with its own classical field.
Keywords: Array; Array; Array; Array